Vocational Students’ Cognitive Engagement in CALLA-Based Instruction in Reading Classroom - Nunun Nurhalimah; Muhammad Reza Pahlevi; Acep Bahrum Kamil (Universitas Majalengka, 2022)
Learning to read is one of the important factors in teaching English. Therefore, students need instructions and strategies that can help them carry out reading learning activities. It resulted several views regarding reading teaching learning instruction in the context of language learning. This study focused on how the students' cognitive engagement in reading narrative texts with the help of CALLA instructions. The participants of the study were five vocational students at one of vocational school in Karawang. This research was conducted using narrative inquiry design and the data were collected through interviews, observation and documentation. To conduct the analysis, this study employed thematic analysis suggested by Braun and Clarke. This study showed that (1) Students have attention on learning classroom, (2) Using dictionary builds students’ resource management learning, (3) Repetition strategy reinforce students’ reading comprehension, (4) Students’ self-elaboration creates them to connect the reading passage. It indicates that CALLA-based instruction engages students cognitively in reading teaching and learning classroom.